2013
DOI: 10.4103/0022-3859.109479
|View full text |Cite
|
Sign up to set email alerts
|

Post total thyroidectomy hypocalcemia

Abstract: CSH after TT is multi-factorial, and a combination of factors (Hypocalcemia prediction score > 3) can be used to predict it so as to discharge patients within 24 hours after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…33 Biochemical postoperative hypocalcemia after total thyroidectomy. 34 In our study it is also found the same result. But in that study Pradeep et al found age was not significant in postoperative hypocalcemia.…”
Section: Discussionsupporting
confidence: 87%
“…33 Biochemical postoperative hypocalcemia after total thyroidectomy. 34 In our study it is also found the same result. But in that study Pradeep et al found age was not significant in postoperative hypocalcemia.…”
Section: Discussionsupporting
confidence: 87%
“…Low post-operative calcium was the only other commonly assessed biochemical factor that showed a statistically significant positive association with transient biochemical hypocalcaemia in the majority of studies. 12,13,22–24,27,28,31,32,36,37,39,44,45 Positive associations were shown with post-operative calcitonin and post-operative albumin but in only one study. 18 Pre-operative vitamin D, magnesium, phosphate, creatinine, calcitonin and thyroid-stimulating hormone levels showed non-significant associations in the majority of studies where investigated.…”
Section: Resultsmentioning
confidence: 85%
“…23 Lombardi et al suggested single serum calcium measurement 12 hours post-operatively after total thyroidectomy. 24 In the present study we used cut off of 7.5 mg% as a predictive factor for development of Hypocalcaemia, which has a sensitivity of 73% & specificity of 84%, as recorded by Pradeep PV et al 25 Lo CY et al used serum calcium level of 7.2 mg% as cut off for defining hypocalcaemia. 26 Another factor closely related to development of post thyroidectomy hypocalcaemia is serum iPTH, which has been reportedly measured in various studies across literature search, both intra-& post-operatively.…”
Section: Discussionmentioning
confidence: 92%